Pediatric parotideomasseteric pilomatrixoma in children - Salzman, Richard; Starek, Ivo; Faisal, Hitari; Tichy, Tomas (Biomedical papers, 2014)
Aims: To review definitive histological diagnoses of patients with great salivary gland tumors with focus on the relatively high incidence of pediatric pilomatrixomas. The authors focus on clinical investigation, imaging methods and fine needle aspiration cytology of pilomatrixomas.Methods: We treated 12 children with great salivary gland masses aged from 6 months to 18 years from 1995 to 2010. The records of these patients were reviewed to determine sex, age, clinical presentation, and histological findings.Results: Among children having true neoplasms, there was a prevalence of carcinomas (6 out of 9), with low-grade mucoepidermoid and acinic cell carcinomas (two each) as the dominating histopathological diagnosis. There was one adenoid cystic carcinoma and one curious undifferentiated carcinoma in a 6 month old baby. Among all 6 benign lesions, accounting for a half of the total, pilomatrixoma was the most common (2 out of 6) diagnosis, representing 17% (2 out of 12) of all salivary gland lumps and 66% (2 out of 3) of all true benign neoplasms.Conclusions: Pilomatrixoma should be included in the differential diagnosis of pediatric parotideomasseteric lumps. Clinical investigation reveals adherence to the skin but not to the underlying tissue. Clinical assessment and ultrasound guided fine needle aspiration cytology in typical findings strongly support the diagnosis. Cytopathologists must be aware of the preliminary diagnosis of a pilomatrixoma to use proper fixation of the smears. In doubts, frozen biopsy must be sent before parotidectomy is performed.
Keywords: pilomatrixoma; benign neoplasms; parotid neoplasms; differential diagnosis